Menyingkap Akar Ideologi Lirik Lagu “Epiphany”: Analisis Tiga Kode Narasi Roland Barthes - Koesworo Setiawan (Badan Pengembangan dan Pembinaan Bahasa, 2026)
This article aims to construct the core meaning, identify the ideological roots, and explain how the ideology of the song